Rehabilitasi Bangunan Dan Saluran Irigasi Di Subak Sembung Kota Denpasar: Indonesia - I Gusti Ayu Widi Agripina; Hari Siswoyo; Sumiyati Sumiyati (Universitas Majalengka, 2023)
Subak Sembung is intended to be the keeper of the green lane area and a large water catchment area. Subak Sembung has an area of 103 ha and a tertiary irrigation canal of 5.1 km. Based on the survey results at the study area conducted in July 2022, there are several damage of the buildings and irrigation canals that had an impact on the supply of irrigation water to rice fields, especially for farmers who have downstream rice fields. Irrigation canals damage causes by the uneven water distribution by farmers. The purpose of this study is to repair and improve the function of buildings and irrigation canals therefore they can facilitate irrigation water supply and be able to reach wider agricultural land. This research was conducted using survey and interview method. The results showed that there was 1 (one) building and 4 (four) irrigation channels damage that were disrupted the irrigation water supply, therefore the rehabilitation cost needed would be Rp. 746,243,500,-. The cost is planned for the next 1 (one) year period.